2016
DOI: 10.1159/000447372
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Denosumab Versus Zoledronic Acid in Patients with Bone Metastases: A Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction: Bone metastases lead to local bone destruction and skeletal complications. Bisphosphonates, particlulaly zoledronic acid (ZA), play a central role in the treatment of bone metastases. Some studies have shown that denosumab may delay and prevent SREs in metastatic bone disease more effectively than ZA; therefore, we systematically reviewed and assessed the safety of denosumab and ZA. Methods: The PubMed, EMBASE, Cochrane Library, Web of Science with Conference Proceedings, Elsevier, and China Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 24 publications
0
35
0
4
Order By: Relevance
“…Chen and Pu (17) recently performed a meta-analysis of randomized controlled trials showing the safety of denosumab versus zoledronic acid in patients with bone metastases. They found that a new primary malignancy occurred significantly more frequently in patients treated with denosumab than with zoledronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and Pu (17) recently performed a meta-analysis of randomized controlled trials showing the safety of denosumab versus zoledronic acid in patients with bone metastases. They found that a new primary malignancy occurred significantly more frequently in patients treated with denosumab than with zoledronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…101,102 Denosumab is associated with AEs other than MRONJ, including hypocalcemia and musculoskeletal pain. 103,104 The risk of developing hypocalcemia as a result of treatment with bisphosphonates or denosumab can be reduced by intake of sufficient dietary or supplemental calcium. 105,106 Risk factors for MRONJ The dominant factor when assessing the likelihood of development of MRONJ is the cumulative exposure of the patient to bisphosphonates or denosumab, considering both the dose per treatment and the number of administrations given from the start of the treatment.…”
Section: Hypercalcemia Of Malignancymentioning
confidence: 99%
“…Nevertheless, Denosumab and bisphosphonates have common side effects such as hypocalcaemia, hypersensitivity to products (skin allergic reactions, hypotension, dyspnea, and angioedema) but also an atypical femur fracture or an osteonecrosis of the jaw …”
Section: Introductionmentioning
confidence: 99%